The Infusion of Notification Design With an Application of Social Media Based on a Internet of Things (IOT) - Candra, Rudi Arif; Saputra, Devi Satria; Ilham, Dirja Nur; Setiawan, Herry; Hardisal, Hardisal (Sinkron : jurnal dan penelitian teknik informatika, 2020)
This study discusses the infusion detection device in a hospital room. This tool is designed to help hospital nurses to cope more quickly to avoid problems due to the infusion. Load cell sensors are used as heavy detectors that send notifications to the nurses through the telegram application that has been installed. The nurse will get a notification message sent to the telegram if the sensor has read the weight. The tool is made using a load cell sensor and NodeMCU Wi-FiESP866 which functions to send notification of the results of sensor data input to the Internet of Things (IOT) platform namely Telegram. Nurses need to be connected to the internet network to get notifications on the telegram. Test results show that the time needed to send and receive notifications on Telegram takes about 2-5 seconds. The message will be sent 3 times, first the infusion WARNING is almost exhausted (alert), second the infusion WARNING is almost exhausted (standby) and the infusion WARNING is almost exhausted (please replace). If the infusion is not replaced by the nurse, it will be warned by Buzzer. However, time can be influenced by the available internet network connectivity. However, time can be affected by the available internet network.